A single balcony for those who 'first touch the bell' in global lenience agreements - Mendes, Dany Rafael Fonseca (2018)
This study, as a whole, assumes the social benefits of market competition, where unethical behavior, such as illegal agreements between market competitors (i.e. cartels), causes problems for the global system of free markets. Because of this socially undesirable conduct, countries have different leniency programs, which idealize solutions that are gaining strength in the fight against cartels worldwide. Moreover, this paper explores the logic behind leniency agreements in the elaboration of amnesty agreements. Furthermore, this study tackles another fundamental problem: the excess of jurisdictions in leniency agreements – which, at the global level, restricts the global system of free market defense. With this problem in mind, this research proposes a solution for the excess of jurisdictions and investigates another approach: a proposal of a "one-stop shop for the first bells", that is, a global system of distribution of unified passwords for leniency agreements that may involve a number of countries.